Pengaruh Kepemimpinan Transformasional Kepala Sekolah Terhadap Disiplin Kerja Guru di SMP Negeri 1 Doloksanggul Tahun Ajaran 2025/2026 - Selly Nainggolan; Betty A.S Pakpahan; Tahoma F. Siburian; Endang J. Manullang; Abai Manupak Tambunan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study explains that the principal’s transformational leadership has been implemented in an effort to improve teachers’ work discipline at SMP Negeri 1 Doloksanggul. The purpose of this study is to determine the influence of the principal’s transformational leadership on teachers’ work discipline at SMP Negeri 1 Doloksanggul in the 2025/2026 academic year. The method used in this research is an inferential quantitative method. The population in this study consisted of all teachers of SMP Negeri 1 Doloksanggul, totaling 50 people, and this research used a population study. The research instrument was a closed questionnaire. The results of the data analysis show that there is a positive and significant influence of the principal’s transformational leadership on teachers’ work discipline, and the principal’s transformational leadership has been implemented at SMP Negeri 1 Doloksanggul in the 2025/2026 academic year. This is proven through the following data analysis: (1) Analysis prerequisite tests: (a) the normality test obtained an Asymp. Sig. (2-tailed) value of 0.200 > 0.05; (b) the linearity test obtained a significance value of deviation from linearity of 0.368 > 0.05. (2) Hypothesis testing: (a) the correlation test between variables X and Y obtained rxy = 0.323 > rtable = 0.279, indicating a positive relationship between variable X and variable Y; (b) the significance test obtained tcount = 2.363 > ttable = 2.021, indicating a significant relationship between variable X and variable Y; (c) the regression equation test obtained the regression equation Ŷ = 51.336 + 0.390X; (d) the coefficient of determination test (r²) = 10.4%; (e) hypothesis testing using the F test obtained Fcount > Ftable, namely 5.584 > 4.08. Thus, H0 is rejected and Ha is accepted, meaning that the study concludes that there is a positive and significant influence of transformational leadership on teachers’ performance at SMP Negeri 1 Doloksanggul in the 2025/2026 academic year, with a contribution of 10.4%. Transformational leadership itself is a leadership style that inspires and motivates members of an organization to achieve higher performance and organizational goals through vision, motivation, and positive change.